ALS3 Expression as an Indicator for Candida albicans Biofilm Formation and Drug Resistance - Deng, Keke; Jiang, Wei; Jiang, Yanyu; Deng, Qi; Cao, Jinzhong; Yang, Wenjie; Zhao, Xuequn (Frontiers in Microbiology, 2021)
Resistance caused by the formation of the Candida albicans (C. albicans) biofilm is one of the main reasons for antifungal therapy failure. Thus, it is important to find indicators that predict C. albicans biofilm formation to provide evidence for the early prevention and treatment of the C. albicans biofilms. In this study, C. albicans samples were selected from C. albicans septicemia that were sensitive to common antifungal agents. It was found that the agglutinin-like sequence 3 (ALS3) gene was differentially expressed in free, antifungal, drug-sensitive C. albicans. The average ALS3 gene expression was higher in the C. albicans strains with biofilm formation than that in the C. albicans strains without biofilm formation. Then, it was further confirmed that the rate of biofilm formation was higher in the high ALS3 gene expression group than that in the low ALS3 gene expression group. It was found that C. albicans with biofilm formation was more resistant to fluconazole, voriconazole, and itraconazole. However, it maintained its sensitivity to caspofungin and micafungin in vitro and in mice. Further experiments regarding the prevention of C. albicans biofilm formation were performed in mice, in which only caspofungin and micafungin prevented C. albicans biofilm formation. These results suggest that the expression level of ALS3 in C. albicans may be used as an indicator to determine whether C. albicans will form biofilms. The results also show that the biofilm formation of C. albicans remained sensitive to caspofungin and micafungin, which may help to guide the selection of clinical antifungal agents for prevention and therapy.